2015
DOI: 10.1177/1329878x1515500115
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Media Sport Consumption: Online Gambling in European Football

Abstract: This article explores the intersections between sports bodies, media companies and gambling industries in European football. While betting, communication and sport have maintained an ongoing relationship for over two centuries, this article argues that the digitalisation of betting platforms has reconfigured the links between the traditional actors and created a new ‘online football betting ecology’. We elaborate on the intricate relationships of betting sites with top European football institutions via sponso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…This situation has produced a dependency on gambling-origin money by means of sponsorship deals for competitions, media corporations, and even sport journalists (Bunn et al, 2019). The case of sports journalists in Spain is particularly troublesome, as one study found that among the top 10 sports writers in terms of number of followers on Twitter , all of them had in the past (or still had) gambling endorsements (Lopez-Gonzalez & Tulloch, 2015). The legalisation of online betting in the United States is very likely to similarly incentivise networks (and especially, ESPN ) to foster an in-play betting-friendly industry in their broadcasts, particularly considering their declining viewing rates (Deitsch, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This situation has produced a dependency on gambling-origin money by means of sponsorship deals for competitions, media corporations, and even sport journalists (Bunn et al, 2019). The case of sports journalists in Spain is particularly troublesome, as one study found that among the top 10 sports writers in terms of number of followers on Twitter , all of them had in the past (or still had) gambling endorsements (Lopez-Gonzalez & Tulloch, 2015). The legalisation of online betting in the United States is very likely to similarly incentivise networks (and especially, ESPN ) to foster an in-play betting-friendly industry in their broadcasts, particularly considering their declining viewing rates (Deitsch, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious association between elite sport and gambling is seen in gambling advertising connected with sport events. The advertising revenues from regulated gambling companies have become a significant source of funding for the sports sector Lopez-Gonzalez & Tulloch, 2015;Milnes, 2018). In the UK, the dominant position of the gambling industry as sponsors, especially of football, has been critically discussed in recent years (Bunn et al, 2018;Lewanczik, 2019).…”
Section: Sport Clubs As Workplaces and Their Relation To The Gamblingmentioning
confidence: 99%
“…If a user clicks on it and access the betting site, the newspaper as an affiliate marketer will get 30% of the money that user has lost betting (Affiliates United, 2014). To boost the number of users clicking on it, the paper publishes next to it a news article featuring Real Madrid on the eve of a match against Manchester United with the following headline: “Cristiano Ronaldo scored in 4 of his last 5 visits to Old Trafford.” Now, the journalist shares the link to that piece of news on Twitter , predicting a goal from Ronaldo, with a nonnegligible likelihood that he or she is in business with a betting company, according to what was found in a 2014 sample of the 10 most followed sports journalists in Spain (Lopez-Gonzalez & Tulloch, 2015). The tweet might be read by someone at home, or even in the stands of a stadium as the game is being played, in which case a betting company might have sponsored the installation of high-speed wi-fi connection to facilitate bets (Hills, 2014).…”
Section: The Marketing Of Online Sports Bettingmentioning
confidence: 99%